Pola Erupsi Gigi Susu dan Gigi Tetap pada Anak Desa IDT Kabupaten Pandeglang dan Serang - Herawati Djoharnas (Journal of Dentistry Indonesia, 2015)
Research on deciduous and permanent tooth eruption pattern for children of developing countries is very limited. The aim of this study is to find out, whether there is a difference between tooth eruption of children in developed countries and in Indonesia. For this purpose 456 children under five and 1120 school children with an age of 6 - 15 years were examined. The result showed that the fine of tooth eruption of children in Indonesian is longer than that of children in developed countries.